Factors Hindering Nursing Care Documentation: A Scoping Review - Mardiati Mardiati; Iis Rahmawati; Nurfika Asmaningrum (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nursing documentation is a critical element in ensuring patient safety, continuity of care, and professional accountability. However, the practice of documentation often encounters multiple challenges, including insufficient training, high workloads, limited resources, and the lack of clear operational guidelines. These barriers can impact the quality of care and patient safety, necessitating an in-depth exploration to understand and address them effectively. This scoping review aims to identify and analyze the factors hindering nursing care documentation, focusing on technical, individual, organizational, and contextual barriers across various healthcare settings. This review includes studies involving nurses and the factors affecting nursing care documentation. The concepts reviewed include barriers to documentation, such as individual, technical, organizational, and contextual obstacles. The context encompasses various healthcare settings, including hospitals, clinics, and community healthcare services across different countries. A comprehensive literature search was conducted using databases such as PubMed, ScienceDirect, Google Scholar, and ProQuest. Articles published between January 2020 and December 2024 were assessed using the JBI and MMAT critical appraisal tools. The selection process, based on PRISMA guidelines, identified 15 eligible articles for analysis. Key barriers to nursing documentation include inadequate training, low technological literacy, high workloads, infrastructure limitations, low motivation, and the absence of consistent documentation guidelines. These barriers affect the quality and accuracy of documentation, with implications for patient safety and service efficiency. Additionally, the findings highlight the need for improved supervision, auditing, and investments in documentation technology. Barriers to nursing care documentation require holistic interventions, including continuous training, technological infrastructure enhancement, and the implementation of clear operational guidelines. Further research is needed to explore effective solutions and their applications in diverse contexts.